Efficacy and Safety of Tranexamic Acid in Resection and Endoprosthetic Reconstruction of Distal Femoral Osteosarcomas in Children: A Retrospective Cohort Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Background: This study aimed to investigate the effect of intravenous tranexamic acid (TXA) on blood loss and transfusion rates in children who underwent resection and endoprosthetic reconstruction of distal femoral osteosarcomas. Methods: The medical records of 56 patients who underwent resection and endoprosthetic reconstruction for distal femoral osteosarcomas between 2017 and 2019 were retrospectively reviewed. Patients were divided into 2 groups: group 1 consisted of 25 patients (11 male and 14 female, mean age 15.2 +/- 3 y) who received preoperative 15 mg/kg intravenous TXA, and group 2 consisted of 31 control patients (18 male and 13 female, mean age 14.3 +/- 2.6 y) who did not receive TXA. The groups were compared based on their total blood loss, intraoperative blood loss, hidden blood loss, postoperative drain output, transfusion requirements, preoperative and postoperative hemoglobin (Hb) and hematocrit (Htc) difference, length of hospital stays, operative time, and complications. Results: The mean total blood loss was lower in intravenous TXA group (1247.5 +/- 300.9 mL) when compared with control group (1715.7 +/- 857.0 mL) (P=0.018). The mean intraoperative blood loss in intravenous TXA group (386 +/- 109 mL) was lower than that in control group (977.4 +/- 610.7 mL) (P<0.001). Postoperative drain output at 24 and 48 hours was 198.0 +/- 61.8 and 72.4 +/- 27.4 mL in intravenous TXA group, respectively, and was low compared with 268.4 +/- 118.2 and 117.1 +/- 67.8 mL in control group (P=0.028 and 0.006). The rate of patients requiring transfusion was significantly lower in intravenous TXA group (56%) than in control group (83.9%). Preoperative and postoperative 6, 24, and 72 hours Hb and Htc differences were significantly lower in intravenous TXA group [(-1.7 +/- 1.8 g/dL PPP<0.001, for Hb) (-5.7 +/- 4.6, P<0.001; -6.9 +/- 4.0, P<0.001; -9.6 +/- 9.1, P<0.001, for Htc)]. Intravenous TXA group had shorter hospital stay time in comparison to control group (P<0.001). The operative time was significantly longer in the control group (P<0.05). No increase in pulmonary embolism or venous thromboembolism rate was observed with intravenous TXA use. Conclusion: We conclude that administration of intravenous TXA reduces intraoperative and postoperative blood loss, transfusion rates, and hospital stay in resection and endoprosthetic reconstruction of the distal femoral osteosarcomas in children. Type of Study: This was a retrospective comparative study.
Keywords: tranexamic acid; sarcoma; bone tumor; distal femur; blood management; children; BLOOD-LOSS; KNEE ARTHROPLASTY; TRANSFUSION; PREDICTION; HIP